Sanitasi Total Berbasis Masyarakat (STBM Dengan Diare Pada Balita - Jeffrey Surya (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
The incidence of diarrhea is a health problem that is found in many parts of the world. The United Nations Children's Fund (UNICEF) states that one in ten children worldwide dies from diarrhea in 2015. Diarrhea in children under five is caused by two main factors namely behavioral factors such as non-exclusive breastfeeding and environmental factors such as poor sanitation and personal hygiene Community Based Total Sanitation (STBM) has five pillars, namely open defecation, washing hands with soap, managing drinking water, and household food, securing household waste, and securing household liquid waste. The implementation of the five pillars (STBM) will facilitate efforts to improve access to improved community sanitation so that in the long run it can reduce morbidity and mortality due to poor sanitation